Does bony consolidation guarantee functional recovery after tibial nonunion?: Impairments and rehabilitation needs assessed by motion analysis - Armbruster, Jonas; Fuchs, Lea Viola; Trinler, Ursula; Reiter, Gregor; Grützner, Paul Alfred; Freischmidt, Holger (Gait & posture, 2026)
Objective - This study aims to quantify residual functional limitations and to identify rehabilitation needs in adults with healed tibial nonunions using comprehensive motion analysis. - Design - Clinical-experimental cohort study. - Methods - Subjective status was captured with the Lower Extremity Functional Scale, Short-Form 36, and a Numeric Rating Scale for pain. Objective performance was profiled via marker-based gait analysis and two functional tasks - single-leg stance and squat. Key read-outs comprised temporal-spatial gait metrics, the Gait Profile Score, and individual Gait Variable Scores. - Results - Thirty-one adults were analysed (twelve with healed tibial nonunions and nineteen with uncomplicated fracture healing). Compared with controls, the nonunion group showed markedly lower functional scores and higher pain. Leg length inequality was greater and strongly related to pain intensity. Motion analysis documented wider step width, higher stride-length variability, and other indicators of gait instability. Functional tests confirmed reduced single-leg balance and limited joint range during squatting. - Conclusion - Bone union does not guarantee functional recovery. Patients who overcome tibial nonunion continue to display substantial gait and performance deficits that warrant structured, individually targeted rehabilitation programmes guided by motion-analysis findings to restore efficient locomotion and quality of life.
Online verfügbar: 25. September 2025, Artikelversion: 9. Dezember 2025
Gesehen am 06.02.2026